Organizational behavior - Luthans, Fred (McGraw-Hill, 2008)
Organizational Behavior by Fred Luthans was the first mainstream organizational behavior text on the market and continues the tradition of being the most current and up-to-date researched text today. Well known author Fred Luthans is the 5th highest Publisher in Academy of Management Journals, is a senior research scientist with the Gallup Organization, and continues to do research in the organizational behavior area. Organizational Behavior 11th Edition is ideal for instructors who take a resea